Association between suboptimal health status and academic performance: A cross-sectional study of 1,028 medical students in Punjab, Pakistan - Asim, Maleha; Malik, Misbah; Jamil, Aneela; Yasmin, Raheela; Jawwad, Ghazala; Khan, Wajahat Ullah (Universitas Negeri Malang, 2025)
Background: Suboptimal health status (SHS) refers to the transitional period between health and illness, characterized by unexplained symptoms and premature changes in functional status without a known medical diagnosis. Objective: The aim is to examine how often SHS occurs and how lifestyle factors influence both SHS and the academic success of medical students. Methods: A Cross-sectional survey was conducted from February 2024 to September 2024 with first- to fifth-year medical students from four randomly chosen medical colleges in Punjab, Pakistan. The Suboptimal Health Measurement Scale (SHMS V1.0), Pittsburgh Sleep Quality Index (PSQI), and Health-Promoting Lifestyle Scale (HPLS) were used to obtain data. The findings were analyzed using independent t-tests, chi-squared tests, and multivariate logistic regression analyses. Result: Among the 1,028 respondents, 55.4% (570) were classified as healthy and 44.6% (458) as having SHS. Higher levels of physical activity (p < 0.001; OR = 0.87; 95%CI = 0.82–0.92), healthier sleep patterns (p < 0.001; OR = 0.92; 95%CI = 0.89-0.94), and better dietary habits (p = 0.003; OR = 0.95; 95%CI = 0.93-0.97) were negatively associated with SHS. In contrast, increased screen exposure (p = 0.012, OR = 1.03; 95%CI = 1.01-1.06), weight loss (p = 0.001, OR = 1.07; 95%CI = 1.02-1.11), tobacco use (p = 0.028, OR = 1.10; 95%CI = 1.02-1.18), and alcohol consumption (p < 0.001, OR = 1.95; 95%CI = 1.74-2.26) were positively associated with SHS. Students with lower academic performance (GPA < 3.0) also demonstrated higher SHS rates. Conclusion: SHS is common among medical students and is associated with unhealthy lifestyle habits and low academic performance.